Hydrolutos gransabanensis sp.n. (Orthoptera: Anostostomatidae), a new semi-aquatic Lutosini species from Gran Sabana (Venezuela) - Derka, Tomáš; Fedor, Peter; Svitok, Marek; Trizna, Milan (Zootaxa, 2013)
Hydrolutos gransabanensis, a new species of Lutosini (Orthoptera: Anostostomatidae) from the cave Cueva El Tigre (Santa Elena de Uairén, SE Venezuela) is described and figured for both sexes. This is the first record of Hydrolutos spe-cies out of tepui systems. The genus is recently known by 6 apterous species from Venezuelan Guayana region.